THE DESIGN OF ALL-OPTICAL NOT AND OR GATES BASED ON 2×1 MMI COUPLERS ON AN SOI PLATFORM - Thanh, Le Trung (Vietnam Journal of Science and Technology, 2012)
In this paper, a general theory for designing optical logic gates based on 2x1 multimode interference (MMI) structures is presented. Designsfor a set of optical logic gates using silicon on insulator (SOI) channel waveguide structures areproposed and optimised. It is shown that this single structure can be used to implement a variety of optical logic and other functions. These devices are optimised by the three dimensional propagation method (3D-BPM).Keyword.  optical logic gates, silicon on insulator, optical  devices, multimode interference couplers.